Assessment of Sports Development Patterns, Mountain State Physical Training Approaches, and Physical Ability - Suratmin; I Putu Darmayasa; Hanik Liskustyawati (Jurnal Pendidikan dan Pengajaran, 2023)
The Provincial Sports Week (Porprov) which is held by KONI Bali Province every two years is attended by 9 (nine) Regencies or Cities. One of the sports that contributed the most medals was athletics, both in road, running, jumping and throwing as measured and individual sports. Management of athletic development patterns it has not been evenly distributed and has experienced a decrease in medal tally. The aim of the study was to analyze the pattern of sports coaching, the physical exercise approach to Njegara Gunung, and the physical abilities of PASI athletes at the Bali Porprov in 2022. This study used a descriptive method with a combination of quantitative and qualitative data, through surveys. The research sample was 49 athletics athletes participating in Porprov Bali in 2022. Data obtained through observation, interviews, questionnaires, tests or measurements, archives, and documentation. The data analysis used is product moment correlation and data triangulation analysis to examine the pattern of coaching and physical training approaches for PASI Bali athletes.The results of the research found the creation of patterns and strategies for athletic development through the management of district or city PASI administrators in the province of Bali to achieve the goals of achievement coaching, setting targets, and targets in developing coaching models, physical training approaches and improving regional athletic achievements.